THE FINITE ELEMENT ANALYSIS ON HEXAGONAL RING UNDER SIMPLE LATERAL LOADING - SAID, MD RADZAI; YAAKOB, MOHD YUHAZRI (Global Engineers and Technologists Review, 2012)
Lateral crushing of hexagonal ring under quasi-static loading were analysed using ABAQUS/Standard Finite Element (FE) Method package. The modes of deformation and loaddisplacement characteristics were predicted and the same were compared with experimental results. The material modelling of elastic-perfectly plastic and nominal stress-plastic strain were compared. The experimental results found that the quarter model using CPE6H with elastic-perfectly plastic material is good enough to obtain a satisfactory result.